Optimized Image Extracting Algorithm from Original Image using Ground Truth - Isidro, Ariel; Fajardo, Arnel (Proceedings (International Conference on ICT for Smart Society. Online), 2019)
Information technology has been playing major roles in the field of medical research and analysis in diagnosing as well as treatment of diseases. Colon cancer is among one of the diseases to be identified effectively and accurately. The scarcity of datasets however hinders the progress of researchers. This paper introduces an algorithm that extracts image from an original image using a ground truth. The algorithm used Python programming language in string slicing. The algorithm was able to extract both polyp and non-polyp images and decreases 8% of the time it takes than original image. Furthermore, this algorithm is useful in creating future studies.